The Role of the COBIT 5 Framework in IT Governance - Triloka Mahesti; Muhamad Sidik (Yayasan Kita Menulis, 2026)
The rapid growth of information technology requires effective governance to ensure alignment with organizational goals, often evaluated using the COBIT 5 framework. This study audits SIKADU, the information system at SMKN 2 Salatiga, to assess its support for strategic objectives across five domains: MEA, DSS, APO, BAI, and EDM. The findings reveal an overall capability level of 2 (Managed Process), falling short of the expected level 3. Specific scores show that while the DSS domain reached level 3.0, others lagged behind, including MEA (2.3), APO (1.8), EDM (1.5), and BAI (1.3). This performance gap indicates that while processes are managed, they are not yet fully standardized. Consequently, the audit provides a strategic roadmap and actionable recommendations to bridge these gaps, helping SMKN 2 Salatiga refine its IT governance and improve the maturity of its SIKADU system.